Eurocrisis: The European Integration as a Neoliberal Project - Szedlacsek, Eszter (Identities: Journal for Politics, Gender and Culture, 2017)
Author(s): Eszter Szedlacsek Title (English): Eurocrisis: The European Integration as a Neoliberal Project Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 14, No. 1 (Winter 2017) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 129-135 Page Count: 7 Citation (English): Eszter Szedlacsek, “Eurocrisis: The European Integration as a Neoliberal Project,” Identities: Journal for Politics, Gender and Culture, Vol. 14, No. 1 (Winter 2017): 129-135.